Latin America at a time of great political turmoil - Borón, Atilio (Universidad Nacional de Villa María, 2017)
Many analysts and observers of the international scene express their apprehension before a world that approaches recklessly to a third world war. There are three features of the international system that offer some interpretive clues to understand this escalating warrior that, incidentally, did not start Trump but comes from before. In the first place a critical factor is the instability of the global geopolitical balance, element that we developed in this writing. A second factor, also thematized here, is the increasing gravitation of the military-industrial-financial complex in the decision-making process of the US government and, to a lesser extent, of its European allies. Finally, a third element that drives wars is what an author like Michael Klare has called "the hunt for natural resources. In this scenario where the war - or the threat of its outbreak - is the backdrop on which international relations develop, Latin America and the Caribbean play a very important role.